Low-frequency diffusion noise in resistive-switching memories based on metal-oxide polymer structure - Rocha, P. R. F. (2013)
Low-frequency noise is studied in resistive-switching memories based on metal–oxide polymer diodes. The noise spectral power follows a 1/fγ behavior, with γ = 1 in the ohmic region and with γ = 3/2 at high bias beyond the ohmic region. The exponent γ = 3/2 is explained as noise caused by Brownian motion or diffusion of defects which induce fluctuations in diode current. The figure of merit to classify 1/f noise in thin films has an estimated value of 10−21 cm2/Ω, which is typical for metals or doped semiconductors. This value in combination with the low diode current indicates that the 1/f noise is generated in the narrow localized regions in the polymer between the contacts. The analysis unambiguously shows that the current in bistable nonvolatile memories is filamentary.